Relationship between self-regulation and writing of academic texts with the development of labor skills - Guzmán Yparraguirre, Eddy (Espergesia, 2017)
This article presents the relationship between self-regulation and writing of academic texts with the development of labor skills. For this purpose, literature was reviewed from various sources such as newspaper articles, virtual libraries, and web pages. The study raises the need to train competent professionals who respond to the demands of today’s society. For this reason, the main theories about self-regulation are discussed. Likewise, the importance of writing in the development of thought and its relationship with self-regulation is also discussed. Moreover, teacher´s participation for the development of self-regulation in university students is also mentioned.